2021
DOI: 10.1111/jar.12928
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards sexuality and related caregiver support of people with intellectual disabilities: A systematic review on the perspectives of people with intellectual disabilities

Abstract: Background: Sexual health remains at risk for people with an intellectual disability.Attitudes towards sexuality, its support and education have an important role in promoting sexual health. The current review aims to provide an overview of the current research on supportive and restrictive attitudes towards sexuality and its support of people with intellectual disabilities themselves.Method: A systematic review was conducted, searching across eight databases. The quality of the studies was assessed with the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…One potential reason why support and education went unmentioned in the present study is that some people with mild to borderline ID have learned to avoid sexuality-based support in order to prevent restrictions and punishment from support staff or relatives following their sexual endeavors [ 27 , 66 ]. However, previous research suggests that people with mild to borderline ID are more receptive to support and education when they have positive experiences with support staff or relatives who match their sexual and educational needs [ 28 ]. Hence, for support and sex education to be successful, they must be aligned with the individual needs of people with ID [ 12 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One potential reason why support and education went unmentioned in the present study is that some people with mild to borderline ID have learned to avoid sexuality-based support in order to prevent restrictions and punishment from support staff or relatives following their sexual endeavors [ 27 , 66 ]. However, previous research suggests that people with mild to borderline ID are more receptive to support and education when they have positive experiences with support staff or relatives who match their sexual and educational needs [ 28 ]. Hence, for support and sex education to be successful, they must be aligned with the individual needs of people with ID [ 12 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research suggests that people with mild to borderline ID are more receptive to support and education when they have positive experiences with support staff or relatives who match their sexual and educational needs [ 28 ]. Hence, for support and sex education to be successful, they must be aligned with the individual needs of people with ID [ 12 , 28 ]. The fact that people with mild to borderline ID prioritize dating and relationships, as shown in this and other studies [ 67 ], indicates that support and education should also prioritize these social dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown variations in the beliefs, perceptions and attitudes of parents and caregivers of adolescents with intellectual disabilities regarding their children's sexuality (de Wit et al, 2022). In this study, the parental responses indicated a low intention to interfere in their children's relationships and to offer young people a great deal of autonomy and freedom, which is not often found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…They are just as likely to be sexually active as peers without disability, but those with a mild to moderate LD/ID are more likely to experience sexual abuse or exploitation, have a higher risk of sexually transmitted infections (STIs), and are less likely to use contraception. They are also less likely to receive sexual health education, perhaps due to societal stigma, concern of carers, and possible infantilising attitudes towards people with an LD/ID (Brown et al., 2020; de Wit et al., 2022). There can also be issues with understanding when the education is not appropriately translated (Finlay et al., 2015).…”
Section: Introductionmentioning
confidence: 99%